Epigenetic therapy approaches in non-small cell lung cancer: Update and perspectives. Issue 12 (1st December 2016) - Schiffmann, Insa; Greve, Gabriele; Jung, Manfred; Lübbert, Michael
ABSTRACT: Non-small cell lung cancer (NSCLC) still constitutes the most common cancer-related cause of death worldwide. All efforts to introduce suitable treatment options using chemotherapeutics or targeted therapies have, up to this point, failed to exhibit a substantial effect on the 5-year-survival rate. The involvement of epigenetic alterations in the evolution of different cancers has led to the development of epigenetics-based therapies, mainly targeting DNA methyltransferases (DNMTs) and histone-modifying enzymes. So far, their greatest success stories have been registered in hematologic neoplasias. As the effects of epigenetic single agent treatment of solid tumors have been limited, the investigative focus now lies on combination therapies of epigenetically active agents with conventional chemotherapy, immunotherapy, or kinase inhibitors. This review includes a short overview of the most important preclinical approaches as well as an extensive discussion of clinical trials using epigenetic combination therapies in NSCLC, including ongoing trials. Thus, we are providing an overview of what lies ahead in the field of epigenetic combinatory therapies of NSCLC in the coming years.